Strategi Pemasaran Produk Dompet D’vat Jaya dengan Pendekatan STP dan Ansoff Matrix - Andriani, Rani; Aulawi, Hilmi; Andriyas Kurniawan, Wahyu (Jurnal Kalibrasi, 2025)
The increasingly competitive business environment, particularly in the fashion and accessories industry, requires MSMEs such as D’vat Jaya to design effective and adaptive marketing strategies in order to survive and grow. This study aims to formulate marketing strategies for D’vat Jaya using STP (Segmentation, Targeting, Positioning) analysis and the Ansoff Matrix to enhance its competitiveness in the market. The research employs a descriptive qualitative method with the STP and Ansoff Matrix approaches. Data were collected through in-depth interviews, field observations, and focus group discussions involving the owner, employees, and consumers. The analysis results indicate the need to narrow the market segmentation to students and young working adults, and to implement growth strategies through market penetration using social media and online marketplaces, market development in potential regions such as Bali and Kalimantan, product innovation including new designs and waterproof wallets, and product diversification with complementary items such as pouches and keychains. The integration of STP and the Ansoff Matrix produced a three-stage strategic plan: short-term (0–12 months) focusing on brand strengthening and digital promotion, medium-term (1–3 years) emphasizing product innovation and varied promotional efforts, and long-term (3–5 years) targeting product diversification and market expansion. The implementation of these strategies is expected to enhance brand awareness, expand market reach, and foster sustainable growth for D’vat Jaya.